2023
DOI: 10.1186/s12903-023-03276-5
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 nanoemulgel in prevention of radiation-induced oral mucositis and its associated effect on microbiome: a randomized clinical trial

Basma M. Morsy,
Shahira El Domiaty,
Mohamed A. M. Meheissen
et al.

Abstract: Background Oral mucositis (OM) is recognized as one of the most frequent debilitating sequelae encountered by head and neck cancer (HNC) patients treated by radiotherapy. This results in severe mucosal tissue inflammation and oral ulcerations that interfere with patient’s nutrition, quality of life (QoL) and survival. Omega-3 (ω-3) polyunsaturated fatty acids (PUFAs) have recently gained special interest in dealing with oral diseases owing to its anti-inflammatory, anti-oxidant and wound healin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…A significant reduction in Firmicutes/Bacteroidetes ratio was observed after six weeks in the test group, indicating less microbial dysbiosis. The results demonstrated that topical omega-3 nanoemulgel has a beneficial effect in preventing radiation-induced OM with the possibility of regulating oral microbial dysbiosis ( 50 ).…”
Section: Oral Microbiota Dysbiosis and Pathogenesis Of Hncsmentioning
confidence: 99%
“…A significant reduction in Firmicutes/Bacteroidetes ratio was observed after six weeks in the test group, indicating less microbial dysbiosis. The results demonstrated that topical omega-3 nanoemulgel has a beneficial effect in preventing radiation-induced OM with the possibility of regulating oral microbial dysbiosis ( 50 ).…”
Section: Oral Microbiota Dysbiosis and Pathogenesis Of Hncsmentioning
confidence: 99%